The Role of Muhammadiyah in the Policy for the Protection of Sexual Violence - Moh. Faizin; Sugianto Sugianto; Romlah Romlah (Audito Comparative Law Journal (ACLJ), 2022)
As one of the largest organizations in Indonesia, the attitudes and policies taken by Muhammadiyah affect the life of the nation and state. One of these attitudes is the Role of Muhammadiyah's legal attitude towards the policy of protecting sexual violence. The methodology used in this research is the method of statutory and historical research. The results of the research with this literature study conclude that Muhammadiyah's attitude in responding to the Policy for the Protection of Sexual Violence is very firm, this can be seen from 2 aspects, namely, first, the basis of thought, which is based on the jurisprudence of child protection, then second, Muhammadiyah's attitude towards the PKS Bill, where Muhammadiyah pushed for the immediate ratification of the PKS Bill with a note that there were changes in problematic articles, supported by the facts presented by 'aisyiah, namely the increasing prevalence of sexual violence against women and children. In addition, Muhammadiyah also took a stand against Permendikbud 30 of 2021 regarding the Prevention and Handling of Sexual Violence in Higher Education Environments due to legal defects, so the policy must be revoked. Muhammadiyah in its attitude related to government policies related to the protection of sexual violence always adheres to the Qur'an and Sunnah as the basis for taking a stand for the benefit of the people and the state